Unexpected nutrient influence on the thermal ecophysiology of seaweeds that recently followed opposite abundance shifts. (October 2019) - Piñeiro-Corbeira, Cristina; Barreiro, Rodolfo; Franco, João N.; Cremades, Javier; Cunha, Jacinto; Arenas, Francisco
Abstract: World's oceans are warming, and recent studies suggest that the Iberian upwelling system may be weakening. To understand the potential consequences of both trends, six intertidal seaweeds that recently followed opposite upward and downward abundance shifts in the Iberian upwelling region were exposed for six weeks to conditions simulating present and warmed scenarios, combined with nutrient treatments emulating the influence and absence of the upwelling. Unlike expectations, a high nutrient supply did not ameliorate the effects of warming. Instead, warming slowed down growth in four seaweeds and accelerated the photosynthesis of downward seaweeds only if nutrients were abundant. In a weakened upwelling scenario, nutrient limitation might more strongly influence the performance of both upward and downward seaweeds than warming. With a normally functioning upwelling, warming might be more detrimental to the performance of some downward seaweeds as they might would lose their ability to benefit from the extra nutrient input. Highlights: Oceans are warming worldwide, and the Iberian upwelling system is weakening. Importance of interaction between both trends on seaweed ecophysiology. First time studying effects of both stressors on algae with opposite field trends. Nutrients influence thermal ecophysiology of intertidal seaweeds. Unlike expectations, high nutrient supply did not ameliorate warming effects.